Relations entre catécholamines, lactates et ions chez le sportif - Sebert, P.; Barthelemy, L.; Caroff, J.; Mialon, P. (Science & sports, 1988)
Les concentrations plasmatiques de catécholamines (CA), lactates (La), Na + et K + ont été mesurées au repos et 2 min après un exercice correspondant à environ 70% V˙O 2 max (Pwc 170); les mesures ont été réalisées dans le même temps expérimental sur 13 sportifs entraînés. Les résultats montrent que: 1) l'exercise provoque une augmentation significative de La, de noradréanline (NA), d'adrénaline (A) et K +, 2) des corrélations statistiquement significatives apparaissent entre La, K + et CA. Les résultats sont discutés en fonction des données de la littérature et interprétés en termes de régulation. Dans le cadre de cette étude, une hypothèse de travail est proposée selon laquelle l'augmentation des CA dans le plasma lors de l'exercice musculaire a des effets physiologiques (par exemple acidose, modifications des perméabilités membranaires) qui peuvent être partiellement corrigés par ces mêmes variations de CA. Despite the important role played by catecholamines (CA) during exercise (activation of glycogenolysis, mobilization of free fatty acids, activation of ventilatory and circulatory convections, ionic transfers… and thus muscle contraction) no study, in our knowledge, is dealing with the eventual interactions between plasmatic concentrations of CA, lactate (La) and ions induced by muscular work. For this reason, plasma levels of catecholamines (CA), lactate (La), Na p + and K +p have been measured at rest and 2 min after an exercise corresponding to a cardiac frequency of about 170 bpm (about 70% V˙O 2 max). The measurements (CA: HPLC; La: enzymatic; ions: specific electrodes) have been performed in the same experimental time on 13 trained male subjects (Table I). The results show that: 1) exercise induces (Table II) a significant increase of La, norepinephrine (NE), epinephrine (E) and K +p, 2) highly significant linear correlations appear between La, K + and CA (Table III), 3) no significant correlation was found with Na +. From this results, the following hypothesis is proposed: exercise is accompanied by CA release which can induce vasoconstriction (a effect, NE) and activation of glycogenolysis (b effect, E) at the muscular level. The consequence is an increase of La and thus acidosis. One of the effects of acidosis is to enhance CA release (and thus the above described mechanisms) and to modify ionic concentrations mainly an increase of K +p, the movements of which can be regulated by CA (entry activation by b effect; entry inhibition by a effect). The existence of a K +/H + exchange modulated by a b adrenergic effect can limit acidosis and thus CA release. Thus CA increase in the course of exercise has physiological effects ( via a and b effects), direct or indirect (like acidosis and modifications of ionic membrane permeability) which are corrected, at least in part, by CA variations and balance between a and b effects.